2010
DOI: 10.1182/blood-2010-02-270785
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of mature T-cell and NK-cell lymphoma: an analysis of patients with T-cell lymphoma treated in studies of the German High-Grade Non-Hodgkin Lymphoma Study Group

Abstract: IntroductionMature T-cell and natural killer (NK)-cell lymphomas are rare and heterogeneous diseases following an aggressive clinical course which necessitates immediate therapy. Outcome is generally believed poor although only 1 recent study 1 comprises all major T-cell lymphoma subtypes according to the World Health Organization classification 2,3 with spin-off studies reporting on clinical outcome and prognostic factors of various subtypes. [4][5][6] In contrast to the progress made in the treatment of aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
375
3
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(416 citation statements)
references
References 32 publications
18
375
3
20
Order By: Relevance
“…For the seven chemonaive patients, the ORR was 71.4% and the CR was 42.9%. The results were consistent with results previously described in detail using the CHOP regimen [15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 82%
“…For the seven chemonaive patients, the ORR was 71.4% and the CR was 42.9%. The results were consistent with results previously described in detail using the CHOP regimen [15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 82%
“…However, cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) is not an optimal treatment for these patients with 40% of patients with ALK-positive disease and over 60% of patients with ALK-negative disease failing to be cured using this approach [27]. German investigators have reported an improved failure-free survival when patients receive CHOP plus etoposide [47]. The ACVBP regimen, which includes a high dose consolidation phase after the initial induction, is highly active in diffuse large B-cell lymphoma and has also been utilized in patients with anaplastic large-cell lymphoma [48].…”
Section: Risk-adapted Therapy Of Specific Subtypesmentioning
confidence: 99%
“…The National Comprehensive Cancer Network Guidelines for the treatment of patients recommend a clinical trial as the best initial treatment option [5]. There is some evidence that the combination of CHOP plus etoposide is more effective than CHOP alone [47], and this is the regimen that I favor. Other regimens that have been utilized include CHOP plus alentuzumab [70], CHOP plus denileukin diftitox [71], CHOP plus bortezomib [62], and other intensive regimens, such as ACVBP [73] and Hyper-CVAD [74].…”
Section: Peripheral T-cell Lymphoma Not Otherwise Specifiedmentioning
confidence: 99%
“…The German High Grade Non-Hodgkin's Lymphoma Study Group (DSHNHL) similarly reported on more than 200 patients with T-NHL enrolled onto prospective trials; 3-year event-free survival was best for ALK-positive ALCL (75%) and suboptimal for all other histologies. 2 Attempts to improve outcomes have included autologous or allogeneic hematopoietic…”
Section: Introductionmentioning
confidence: 99%